Isolation and selection of nitrogen-fixing rhizosphere bacteria from vegetable crops - NGUYEN PHUONG THUY; NGUYEN THANH TUU (Society for Indonesian Biodiversity, 2025)
Abstract. Thuy NP, Tuu NT. 2025. Isolation and selection of nitrogen-fixing rhizosphere bacteria from vegetable crops. Biodiversitas 26: 4841-4850. Intensive vegetable cultivation in Vietnam's Mekong Delta heavily relies on synthetic nitrogen fertilizers, causing significant environmental issues. The aim of this study was to identify indigenous nitrogen-fixing bacteria as sustainable biofertilizers, emphasizing their crucial role in enhancing soil health and agro-biodiversity. Rhizospheric soils were collected from 17 local vegetable species, isolating 36 distinct bacterial strains. Initial characterization revealed a numerical dominance of Gram-positive bacteria (>83%), reflecting adaptation to Tra Vinh's unique conditions, and included a filamentous Actinobacteria isolate. The functionally potent Gram-negative isolates exhibited morphological and biochemical characteristics consistent with genera, such as Achromobacter, Stenotrophomonas, and Dyella. Nitrogen fixation screening via micro-Kjeldahl showed activity from 5.89 mg/L to 24.59 mg/L NH4+. Five elite strains, identified through 16S rRNA gene sequencing as Stenotrophomonas sp. SM9.2, Achromobacter sp. IB1.2, Enterobacter hormaechei subsp. xiangfangensis SM18.2, Achromobacter sp. SM9.1, and Dyella sp. SM18.3, demonstrated the highest nitrogen fixation rates. Laboratory bioassays with water spinach (Ipomoea aquatica) confirmed significant plant growth promotion. Notably, Stenotrophomonas sp. SM9.2 increased fresh biomass by 27.7% and shoot length by 16.6%, while Achromobacter sp. IB1.2 improved seed germination by 9.9%. These findings highlight promising candidates for local biofertilizer production and underscore the importance of leveraging indigenous microbial biodiversity for sustainable farming solutions.